2005
DOI: 10.1073/pnas.0504423102
|View full text |Cite
|
Sign up to set email alerts
|

The endophytic fungus Piriformospora indica reprograms barley to salt-stress tolerance, disease resistance, and higher yield

Abstract: Disease resistance strategies are powerful approaches to sustainable agriculture because they reduce chemical input into the environment. Recently, Piriformospora indica, a plant-root-colonizing basidiomycete fungus, has been discovered in the Indian Thar desert and was shown to provide strong growth-promoting activity during its symbiosis with a broad spectrum of plants [Verma, S. et al. (1998) Mycologia 90, 896 -903]. Here, we report on the potential of P. indica to induce resistance to fungal diseases and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
785
1
30

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,151 publications
(848 citation statements)
references
References 39 publications
32
785
1
30
Order By: Relevance
“…[7 ]. The endophytic fungus Piriformospora indica induced systemic resistance in barley without priming for JA-mediated, ET-mediated, or SA-mediated defenses, but was associated with the activation of the glutathione-ascorbate cycle, indicating an increased antioxidative capacity [5]. In some cases, shoots of mycorrhizal plants showed changes in defense-related gene expression in the absence of a pathogen [42 ], but in other cases priming seems to be the dominant mechanism involved in mycorrhiza-induced systemic resistance [9].…”
Section: Priming For Enhanced Defensementioning
confidence: 99%
See 1 more Smart Citation
“…[7 ]. The endophytic fungus Piriformospora indica induced systemic resistance in barley without priming for JA-mediated, ET-mediated, or SA-mediated defenses, but was associated with the activation of the glutathione-ascorbate cycle, indicating an increased antioxidative capacity [5]. In some cases, shoots of mycorrhizal plants showed changes in defense-related gene expression in the absence of a pathogen [42 ], but in other cases priming seems to be the dominant mechanism involved in mycorrhiza-induced systemic resistance [9].…”
Section: Priming For Enhanced Defensementioning
confidence: 99%
“…Classical examples of symbiotic microorganisms are mycorrhizal fungi that aid in the uptake of water and minerals, notably phosphate [1], and Rhizobium bacteria that fix atmospheric nitrogen for the plant [2]. Several other types of beneficial soil-borne microbes, such as plant growth promoting rhizobacteria and fungi, can stimulate plant growth by suppressing plant diseases [3][4][5][6]7 ] or insect herbivory [8 ]. This biological control activity is exerted either directly through antagonism of soil-borne pathogens or indirectly by eliciting a plant-mediated resistance response [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Members of a rare class of cytotoxic alkaloids, asterriquinones D (100a) and C-1 (100b), have been reported from a strain of Aspergillus terreus inhabiting the rhizosphere of the Sonoran desert cactus, Opuntia versicolor. 87a The co-occurrence in this fungal strain of the new spirodione alkaloid, asterredione (102), has led to the proposition that it is biogenetically derived from asterriquinone D (100a) by a hitherto unknown hydroperoxy-mediated p-benzoquinone ring contraction. In an extensive search for natural product-based antidiabetic agents capable of mimicking insulin activity, Salituro et al screened over 5000 microbial extracts of which about 1500 were derived from endophytic fungal strains.…”
Section: Alkaloids and Other N-containing Metabolitesmentioning
confidence: 99%
“…101 When the cereal model plant barley (Hordeum vulgare L.) was infected with P. indica it was found to have several beneficial effects including the growth-promoting activity resulting in enhanced barley grain yield, amended tolerance to mild salt stress, and conferred resistance in barley against root and leaf pathogens. 102 Further studies have demonstrated that the systematically altered "defense readiness" of barley by this endophyte is associated with an elevated antioxidative capacity due to an activation of the glutathioneascorbate cycle, and that the endophyte might induce systemic disease resistance by an as yet unknown signaling pathway, probably involving a small molecule natural product. 103 Based on the data obtained, these authors have suggested consideration of P. indica as a tool for sustainable agriculture.…”
Section: Some Implications Of the Occurrence Of Plant-associated Micrmentioning
confidence: 99%
“…Endophytes can have several functions and/or may change function during their life cycle (Murphy et al 2013, 2014a). Benefits to crop plants infected with endophytic fungi include an increase in seed yield (Achatz et al 2010; Murphy et al 2014b, 2015), enhanced resistance to pathogens and herbivores (Cheplick and Faeth 2009; Murphy et al 2015a) and increased stress tolerance (Waller et al 2005; Rodriguez et al 2009). …”
Section: Introductionmentioning
confidence: 99%